Experimental study of active vibration suppression of flexible structure using modular control patch - Gangbing Song; Schmidt, S.P.; Agrawal, B.N. (1998 IEEE Aerospace Conference Proceedings (Cat. No.98TH8339), 1998)
This paper presents experimental results of vibration suppression of a flexible structure using a miniaturized digital controller, called modular control patch (MCP). The MCP employs a TI-C30 digital signal processor and was developed by TRW for the United States Air Force for future space vibration control. In this research, the MCP is used to implement different control algorithms for vibration suppression of a cantilevered aluminum beam with piezoceramic sensors and actuators. Positive position feedback (PPF) control, strain rate feedback (SRF) control, and their combinations were implemented. Experiments found that PPF control is most effective for single-mode vibration suppression, and two PPF filters in parallel are most effective for multi-mode vibration suppression. Further experiments demonstrated the robustness of PPF control. PPF can achieve effective vibration suppression when there is a 20% error in modal frequency.